TISSUE CULTURE OF SOME IMPORTANT MEDICINAL PLANTS IN THE SUDAN - El-Tigani, Sayadat (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Callus cultures of Calotropis procera, Solenostemma argel, Senna alata L. and Hibiscus sabdariffa were initiated on Murashige and Skoog media. The media were supplemented with indole butyric acid, naphthalene acetic acid and 2,4-D and [6-benzylaminopurine (BAP) or kinetin]. Explants from cotyledonary leaves and hypocotyl tissues were used. C.procera showed a high potentiality for callus initiation when 10 mg/l IBA and 12.5 mg/l BAP were used. The callus developed a large number of roots. No shoot primordials were observed. 2,4-D at 2 mg/l combined with 0.5 mg/l kinetin enhanced callus initiation while 10 mg/l NAA with 12.5 mg/l BAP had slowed callus initiation. The callus initiated from S.argel explants showed a lower growth rate when compared with that of C.procera tissues grown on MS basal media supplemented with 10 mg/l IBA and 12.5 mg/l BAP. S.alata has shown a high potentiality for callus cultures in vitro. The pigmentation of the callus changed with age. Ovule cultures of Hibiscus sabdariffa were initiated on MS media supplemented with 10 mg/l IBA and 12.5 mg/l BA. Initially the haploid callus showed a very slow growth rate. After establishment, the callus has doubled its size in 6 weeks period. Highly organized root-like structures and extensively lignified tracheids were observed in C.procera and S.argel callus tissues. Less organization was observed in S.alata callus tissues. Most of the extracted tissues seem to produce and accumulate the compounds present in the parent plants. Alkaloids, cardinolides and flavonoids were detected in C.procera and S.argel callus tissues. S.alata callus cultures contained high levels of anthraquinones.